2019
DOI: 10.5114/fmpcr.2019.82980
|View full text |Cite
|
Sign up to set email alerts
|

A 3-year retrospective review of corneal ulcers in Hospital Universiti Sains Malaysia

Abstract: Background. microbial keratitis which is also known as corneal ulcer, is a common ocular infection that can result in debilitating monocular visual impairment. identifying the prevalence and the latest trend of the causative agents will be useful in the management of corneal ulcer. Objectives. To evaluate the demographic and epidemiology factors of microbial keratitis at a tertiary hospital in a rural state of malaysia. Material and methods. This is a retrospective review with a total recruit of 137 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 4 publications
3
5
1
Order By: Relevance
“…This conforms with the local sociodemographic profile in which Malay is the major ethnicity and young males are the main workforce in a largely agricultural state, including farmers, fishermen, and laborers. Our results are in line with several other local studies [ 1 , 2 , 5 ]. Koh et al found that diabetes mellitus was a common risk factor for corneal ulcer due to impaired corneal barrier function and delayed epithelial healing [ 10 ].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This conforms with the local sociodemographic profile in which Malay is the major ethnicity and young males are the main workforce in a largely agricultural state, including farmers, fishermen, and laborers. Our results are in line with several other local studies [ 1 , 2 , 5 ]. Koh et al found that diabetes mellitus was a common risk factor for corneal ulcer due to impaired corneal barrier function and delayed epithelial healing [ 10 ].…”
Section: Discussionsupporting
confidence: 94%
“…Local studies in other states of Malaysia with a similar background supported the findings in our study [ 3 , 4 , 5 , 7 ]. Besides that, we also discover the relevance of the abovementioned factors in the higher incidence of fungal keratitis in India and China [ 1 , 5 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations